Greenspace, physical activity and wellbeing in Australian capital cities: How does population size moderate the relationship? - Ambrey, Christopher (My University, 2015)
Objectives: The purpose of this study is to investigate the synergy between greenspace and physical activity and its implications for wellbeing. In particular, how this synergy may depend on population size in the neighbourhood. Study design: Cross-sectional analysis of resident-level responses from the Household, Income and Labour Dynamics in Australia (HILDA) survey for 2013 subset to Australia’s major capital cities linked to Geographic Information Systems (GIS) data. Methods: GIS data on greenspace per capita and Australian Bureau of Statistics data on population size for the neighbourhood are matched to the residents in the HILDA survey on the basis of the Census Collection District in which they reside. A cluster-specific fixed effects model is estimated for the outcomes of mental health and psychological distress. A battery of socio-demographic and location characteristics were also adjusted for. Interaction terms are used to discern the extent to which population size may moderate any synergistic wellbeing benefits associated with physical activity and greenspace. This question is ultimately operationalised as a three-way interaction effect (greenspace × physical activity × population size). Results: The results indicate that physical activity is most strongly and positively associated with mental health (statistically significant at the 1% level), with an estimated coefficient of 0.6307. The results also reveal that physical activity is negatively associated with psychological distress (statistically significant at the 10% level), with an estimated coefficient of -0.2447. Unexpectedly, for both mental health and psychological distress the greenspace and population variables are not found to have separate statistically significant effects. Furthermore, while the results fail to find, on average, the hypothesised synergy between greenspace and physical activity, a closer inspection reveals that this link may depend on the population size of a neighbourhood. The interaction term for greenspace, physical activity and population bears a coefficient estimate of 0.0033, statistically significant at the 5% level in the mental health regression and a coefficient of -0.0032, statistically significant at the 1% level in the psychological distress regression. Conclusion: The results indicate that physical activity is linked differently to mental health and psychological distress. The results initially provide no evidence of the hypothesised greenspace-physical activity synergy. The results provide evidence that this synergy is greater in more in more populated neighbourhoods.
Public Health
Keywords: Health -- Mental; Actvities -- Outdoor activities; Health -- Physical activity; Health -- Wellbeing; Childhood and child development; Health and wellbeing; Actvities; Health; Mental; Physical activity; Outdoor activities; Wellbeing; Childhood and child development; Health and wellbeing